Application and development of biosensors in the detection of transfusion transmitted diseases markers：a review - CHEN Siyi; LIAO Deyu; ZHAO Lin; GAO Feiran; TAN Bin (Zhongguo shuxue zazhi)
Blood transfusion is a common therapeutic measure with indispensable role in clinical medicine. However, there is a risk of transmitting diseases during blood transfusion, such as human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), etc. To reduce these risks and ensure blood transfusion safety, detection of disease markers in blood transfusion is particularly important. Biological sensing technology, with its advantages of high sensitivity, rapid response and portability, has broad application prospects in the detection of disease markers in blood transfusion. However, the biological sensing strategies for detection of disease markers in blood transfusion have not yet been systematically classified or fully discussed. Therefore, this paper first elucidates the common disease markers in blood transfusion and their importance. Then, it focuses on the application of biological sensors in the detection of disease markers in blood transfusion and discusses the challenges faced and the direction of future development in this field.